Norma v frazeologiji in odstopi od nje v besedilih - Kržišnik, Erika (Slavistična revija, 1996)
There are certain problems with normativization of phrasemes as well as with sources of normativization. Invariability of form and meaning, which is one of the basic features of phraseological units, is often broken in usage. Deviation from the norm are grouped depending on whether or not they constitute a mistake. There are various reasons for the incorrect usage of phrasemes as well as various consequences of such usage.
Keywords: frazemi; frazeologija; napake; norma; phraseology; Slovene; slovenščina